Determination of the Annual Optimal Reliable Frequency for Different Transmitter/Receiver Stations Distributed over the Iraqi Territory - Thabit, Samar A.; Hadi, Khalid A.; George, Loay E. (Iraqi Journal of Science, 2021)
This paper aimed to determine the Optimal Reliable Frequency (ORF) that can maintain certain connection link between different transmitter/receiver stations laid over the Iraqi territory. Three different transmitting sites were chosen as tested stations located in the northern, central, and southern regions of Iraq. These sites are Mosul, Baghdad, and Basra, respectively. In this study, the years 2009 and 2014, which represent the minimum and maximum years of solar cycle 24, were chosen to examine the effect of low and high solar activity on the determined ORF. The datasets of the Best Usable Frequency (BUF) were calculated using the ASAPS international communication model. An analytical study was made on the generated BUF parameter dataset of the annual time for the adopted years. Also, an analytical simulation was made for the suggested ORF parameter depending on the BUF parameter datasets. The results of this simulation showed that the suggested ORF parameter can be represented by polynomial equation of different orders. The suggested formula was determined depending on different tested parameters (path length, bearing, time (day) and BUF values). For this purpose, a certain program was built using a visual basic programing language (VB6). The suggested ORF parameter was investigated for the annual time for the three sites of the years 2009 and 2014.